Microsporogenesis of peach (Prunus persica L. Batsch) varieties - Szalay, L.; Timon, B.; Szabó, Z.; Papp, J. (International Journal of Horticultural Science, 2002)
Bud dormancy during winter is a critical factor in peach production in Hungary. The yield is determined basically by the survival rate of flower buds during winter frosts and by their ability to develop normal floral organs. It is important to investigate the genetic basis of slow floral development during dormancy for the purpose of breeding peach varieties with better winter hardiness. The aim of the present research was to examine microsporogenesis in 14 peach varieties during three successive winters in a Hungarian germplasm collection and to study the effectiveness of this method in variety evaluation. There were significant differences in the dynamics of microsporogenesis both between the varieties and between the years. Of the varieties, ‘Mayfire', bred in California, possessed the quickest pollen development rate. The microsporogenesis of `Piroska', a Hungarian local variety, was the slowest. Rapid floral bud development was observed in `Aranycsillag', `Springcrest' and 'Venus'. A medium developmental rate was characteristic of `Babygold 6', Fairlane', `Michelini' and `Red June', while development was slow in 'Champion', 'Early Redhaven', `Redhaven', `Harko' and `Mariska'. Based on these results, the study of microsporogenesis represents a reliable method for the phenological description of peach varieties during dormancy. The application of this method makes it possible to identify varieties and landraces with slow flower bud development, suggesting better winter hardiness.